A Public Policy to Combat School Failure and Dropout in Mozambique - José Bento Aleixo (2021)
The present study entitled “A public policy to combat school failure and dropout in Mozambique: the bilingual education program”, aims to understand the process of implementing Bilingual Education in the Mozambican education system, answering the question “What are the challenges and opportunities for the development of the bilingual education program in Mozambique?” In a research based on the interpretive paradigm, with an exploratory character and a qualitative approach, were analyzed documents related to bilingual education. Through semi-structured interviews with senior members of the Ministry of Education and Human Development, teachers, school directors and members of District Services for Education, Youth and technologies from two districts, one with partner support and the other without partner support, all involved in bilingual education, were collected data that were subjected to content analysis from which it was concluded that language is just one of the factors that cause school waste and dropout. Factors that facilitate the implementation of the bilingual modality are the existence of human resources, both teaching and non-teaching, partners for education and communities in rural areas that pressured the introduction of bilingual classes in schools. While non-acceptance, and the lack of knowledge about the philosophy of this modality and poverty, are inhibiting factors. To reduce the impact of inhibiting factors, it is suggested greater investment in the dissemination and inclusion of Mozambican languages in the training of some professionals such as doctors and journalists